Peran UMKM dalam Meningkatkan PAD: Studi Kasus Perdagangan dan Jasa - Duwi Diyan Pratiwi; Tutik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Small, Micro, and Medium Enterprises (MSMEs) are a strategic sector in developing the economy. In addition, MSMEs are also a place for people to create jobs so that they can reduce poverty. This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in increasing Regional Original Income (PAD), with a case study of the trade and services sector around Semarang State University (UNNES) in 2025 and the importance of policy support and continuous mentoring for MSMEs so that economic potential can be increased in increasing PAD. The research method used in this study is a qualitative approach and uses data collection techniques through interviews, observation, and documentation. The results show that MSMEs around UNNES have a significant influence on PAD through payment of levies, local taxes, and job creation. In addition, the relationship between the local government, the university, and MSME actors is also a very important factor in driving the economic growth of the region.